2017
DOI: 10.1103/physrevx.7.031039
|View full text |Cite
|
Sign up to set email alerts
|

Topological Sound and Flocking on Curved Surfaces

Abstract: Active systems on curved geometries are ubiquitous in the living world. In the presence of curvature, orientationally ordered polar flocks are forced to be inhomogeneous, often requiring the presence of topological defects even in the steady state because of the constraints imposed by the topology of the underlying surface. In the presence of spontaneous flow, the system additionally supports long-wavelength propagating sound modes that get gapped by the curvature of the underlying substrate. We analytically c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
114
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 86 publications
6
114
3
Order By: Relevance
“…Ellis [16] studied the effect of self-propulsion and curvature on the degree of defect unbinding. On the other hand, curvature can induce spontaneous flow and flocking [22][23][24][25][26][27][28]. Sanchez and coworkers [22] experimentally studied selfpropelled microtubule bundles on curved surfaces and reported the spontaneous generation of a streaming flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis [16] studied the effect of self-propulsion and curvature on the degree of defect unbinding. On the other hand, curvature can induce spontaneous flow and flocking [22][23][24][25][26][27][28]. Sanchez and coworkers [22] experimentally studied selfpropelled microtubule bundles on curved surfaces and reported the spontaneous generation of a streaming flow.…”
Section: Introductionmentioning
confidence: 99%
“…For high curvature, Bruss and coworkers [24] found that particles converge to a common orbit to form symmetrybreaking microswarms. Shankar et al [25] found that curvature and active flow together result in symmetryprotected topological modes that get localized to special geodesics on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…We numerically calculate its band structure and eigenvectors, and demonstrate that they exhibit nonzero topological invari-ants with the corresponding edge modes. Possible relation to non-Hermitian topological phenomena is also discussed.Topological edge modes of active matter have been recently discussed by several authors [19,[35][36][37]. There, the presence of nonzero net vorticity of the active flows, which can act as an effective magnetic field, was crucial to support topological edge modes reminiscent of the quantum Hall effect [1,38].…”
mentioning
confidence: 99%
“…To simplify the problem, we ignore the terms including λ 2,3 and also the diffusive terms that contain the second-order derivative. This condition can be met in a variety of active systems [35,36,50]. We also assume that the pressure P is proportional to ρ as appropriate for an ideal gas.…”
mentioning
confidence: 99%
“…We consider two geometries: a spherical surface in which the region of lower motility covers one hemisphere or a smaller surface area, and a 2D planar surface with periodic boundary conditions, in which one half of the surface is associated with a lower motility. We will focus mainly on the topology of the compact sphere, since it naturally gives rise to only a single interface, and has also recently attracted interest due to its rich curvature-and topology-induced active-particle dynamics [39][40][41][42][43][44][45][46]. However, for the membrane-formation process reported here, the spherical topology is not a crucial ingredient: indeed, we will show that self-encapsulation at the interface between two different motilities also occurs similarly for rod motion in the plane, and that in fact the aligning interactions are the crucial factor.…”
Section: Introductionmentioning
confidence: 99%